Book Review: Visioning a Mi’kmaw Humanities: Indigenizing the Academy - Tompkins, Joanne (Journal of the Canadian Association for Curriculum Studies, 2018)
Visioning a Mi’kmaw Humanities: Indigenizing the Academy is intended to create discussions and describe actions that will challenge the colonial narrative and create more inclusive humanities. Aimed at both Indigenous and Settler educators, the beautifully edited book uses the metaphor of a basket to suggest the weaving of Mi’kmaw knowledge systems with Eurocentric knowledge systems, a weaving that is necessary to create a trans-systemic concept of the humanities that will ultimately decolonize and transform the academy. Visioning Mi’kmaw humanities can create the emergence of education systems which create pride, confidence, belonging and educational success for Indigenous students and teachers. This kind of education system will also benefit non-Indigenous students and teachers with the same gifts and lead to the reconciliation we so urgently seek.